Long-term follow-up of an infant with hypoxic-ischemic encephalopathy treated with hypothermia therapy - Melda, Melda (Indonesian Pediatric Society Publishing House, 2022)
Perinatal asphyxia is one of the most common causes of newborn mortality, with an incidence of two to five cases per 1,000 live births in developed countries and tenfold in developing countries.1,2Lack of oxygen at birth may cause hypoxic ischemic encephalopathy (HIE) with severe neurological consequences, such as cerebral palsy, global developmental delay, blindness or visual defects, hearing loss or deafness, and other comorbidities. Hypothermia therapy is currently the only management option for HIE included in neonatal intensive care unit (NICU) protocols.